2014
DOI: 10.1016/j.celrep.2014.09.051
|View full text |Cite
|
Sign up to set email alerts
|

Host Cell Factor-1 Recruitment to E2F-Bound and Cell-Cycle-Control Genes Is Mediated by THAP11 and ZNF143

Abstract: Summary Host cell factor-1 (HCF-1) is a metazoan transcriptional co-regulator essential for cell cycle progression and cell proliferation. Current models suggest a mechanism whereby HCF-1 functions as a direct co-regulator of E2F proteins, facilitating the expression of genes necessary for cell proliferation. In this report, we show that HCF-1 recruitment to numerous E2F-bound promoters is mediated by the concerted action of zinc finger transcription factors THAP11 and ZNF143, rather than E2F proteins directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
55
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 58 publications
1
55
2
Order By: Relevance
“…This observation is consistent with in vitro electrophoretic mobility shift assays (EMSAs) indicating that mutations in the TCCCA motif interfere with ZNF143 DNA binding activity. Additionally, we observed significant depletion of THAP11 and HCFC1 chromatin occupancy, consistent with our previous observation of THAP11/HCFC1 subcomplex dependency on ZNF143 (21). An AGC mutation in the ACTACA submotif (mutA1) had a similar effect on THAP11 and HCFC1 occupancy; however, ZNF143 binding was affected less severely at the ESCO2 and AP2S1 promoters than with the TTC mutation (mutB1) (Fig.…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…This observation is consistent with in vitro electrophoretic mobility shift assays (EMSAs) indicating that mutations in the TCCCA motif interfere with ZNF143 DNA binding activity. Additionally, we observed significant depletion of THAP11 and HCFC1 chromatin occupancy, consistent with our previous observation of THAP11/HCFC1 subcomplex dependency on ZNF143 (21). An AGC mutation in the ACTACA submotif (mutA1) had a similar effect on THAP11 and HCFC1 occupancy; however, ZNF143 binding was affected less severely at the ESCO2 and AP2S1 promoters than with the TTC mutation (mutB1) (Fig.…”
Section: Resultssupporting
confidence: 79%
“…Thus far, data from in vitro experiments have suggested that THAP11 and ZNF143 compete for binding to these DNA sequences (28). In contrast to these results, observations in our laboratory suggest that, in vivo, THAP11, ZNF143, and HCFC1 are mutually dependent on chromatin associations at gene promoters containing the SBS2 motif and cooccupy the same genomic loci (21). Thus, the mechanism of THAP11 binding to chromatin and the exact target sequence that its THAP domain recognizes remain uncertain.…”
contrasting
confidence: 55%
See 3 more Smart Citations